Predicting Well-Being Among the Elderly: The Role of Coping Strategies - Galiana, Laura; Tomás, José M.; Fernández, Irene; Oliver, Amparo (Frontiers in Psychology, 2020)
Objectives This study aims to offer a wider view on the role of coping strategies on elderly’s well-being by means of literature-based competitive structural equation models (SEMs). Methods 857 older adults were surveyed. Measures included Ryff’s scales of Psychological Well-being and the Coping Strategies Questionnaire. Competitive SEMs were tested. Results In the retained model, the religious coping dimension was removed, and the remaining dimensions were defined by problem- and emotion-focused coping, which explained both psychological and subjective well-being factors (χ2(46) = 165.910, p < 0.001; CFI = 0.906; GFI = 0.957; RMSEA = 0.058 [0.048,0.067]). Discussion Results pointed to the relevance of coping strategies for achieving adequate well-being, with emotion-focused coping strategies being the ones with negative and highest predictive power over the two dimensions of well-being. Interventions aiming at improving old people’s well-being should, put their focus on decreasing the use of emotion-coping strategies.